Pertanggungjawaban Pidana dalam Tindakan Medis Tanpa Informed Consent yang Mengakibatkan Kematian Pasien - Imma Apriana; Vieta Imelda Cornelis; Vallencia Nandya Paramitha; Andi Hayyun Abiddin (Universitas Malahayati, 2026)
ABSTRACT Informed consent is a fundamental principle in medical practice, closely related to the protection of patients’ rights to bodily autonomy and free, informed decision-making. However, medical procedures performed without valid consent are still encountered, whether due to administrative negligence or emergency circumstances that often give rise to legal controversy. This study aimed to analyze the forms of criminal liability of medical practitioners and healthcare professionals for medical actions performed without Informed consent that result in the loss of a patient’s life. This normative juridical research employs statutory and conceptual approaches by examining Law Number 1 of 2023 on the Indonesian Criminal Code, Law Number 17 of 2023 on Health, and Minister of Health Regulation Number 290/MENKES/PER/III/2008 concerning Consent to Medical Treatment. The study is complemented by doctrinal analysis and comparative perspectives from common law and civil law systems. Primary, secondary, and tertiary legal materials were collected through library research and analyzed descriptively and qualitatively using deductive reasoning to assess normative consistency and formulate legal prescriptions regarding criminal liability for medical actions performed without informed consent resulting in a patient’s death. This study indicated that informed consent serves as a primary determinant of the legality of medical actions. The absence of valid consent may qualify a medical intervention as an unlawful act and reinforce the element of fault, particularly in cases involving patient death. Criminal liability is generally constructed as professional negligence; however, under certain circumstances, it may extend to intentional conduct when actions are performed with awareness of significant risks, without consent, and outside emergency conditions. Informed consent constitutes both a prerequisite for the legality of medical interventions and a manifestation of patients’ rights. Its absence may give rise to criminal liability, especially when resulting in death and where fault or violations of professional standards are established. Strengthening documentation practices, clarifying standard operating procedures, and enhancing patient education and communication between medical practitioners, healthcare professionals, and patients are essential to ensure proper implementation. Keywords: Informed Consent, Patient’s Life, Criminal Liability, Medical Practitioners, Healthcare Professionals. ABSTRAK Informed consent merupakan prinsip fundamental dalam praktik kedokteran yang berkaitan erat dengan perlindungan hak pasien atas otonomi tubuh dan pengambilan keputusan bebas serta sadar. Namun, masih ditemukan tindakan medis yang dilakukan tanpa persetujuan yang sah, baik karena kelalaian administratif maupun alasan kedaruratan yang kerap menimbulkan perdebatan hukum. Untuk menganalisis bentuk pertanggungjawaban pidana tenaga medis dan tenaga kesehatan atas tindakan medis yang dilakukan tanpa Informed consent yang mengakibatkan hilangnya nyawa pasien. Penelitian yuridis normative ini menggunakan pendekatan perundang-undangan, konseptual, dengan menelaah Undang-Undang Nomor 1 Tahun 2023 tentang KUHP, Undang-Undang Nomor 17 Tahun 2023 tentang Kesehatan, serta Peraturan Menteri Kesehatan Nomor 290/MENKES/PER/III/2008 tentang Persetujuan Tindakan Kedokteran, disertai kajian doktrin dan praktik di negara common law dan civil law. Bahan hukum primer, sekunder, dan tersier dikumpulkan melalui studi kepustakaan dan dianalisis secara deskriptif-kualitatif dengan penalaran deduktif untuk menilai konsistensi norma serta merumuskan preskripsi hukum mengenai pertanggungjawaban pidana tenaga medis dan tenaga kesehatan atas tindakan tanpa Informed consent yang berimplikasi pada hilangnya nyawa pasien. Penelitian ini menemukan bahwa Informed consent merupakan determinan utama legalitas tindakan medis. Ketiadaan persetujuan yang sah mengakibatkan tindakan dikualifikasikan sebagai perbuatan melawan hukum dan memperkuat unsur kesalahan, terutama dalam kasus yang mengakibatkan kematian pasien. Pertanggungjawaban pidana umumnya dikonstruksikan sebagai kelalaian profesional, namun dalam kondisi tertentu dapat mengarah pada kesengajaan apabila tindakan dilakukan dengan kesadaran atas risiko tanpa persetujuan dan di luar keadaan darurat. Informed consent merupakan syarat legalitas tindakan medis dan perwujudan hak pasien. Ketiadaannya dapat menimbulkan pertanggungjawaban pidana, khususnya jika mengakibatkan kematian dan terbukti adanya kesalahan atau pelanggaran standar profesi. Optimalisasi implementasi memerlukan penguatan dokumentasi, kejelasan SOP, serta peningkatan edukasi dan komunikasi antara tenaga medis, tenaga kesehatan dan pasien. Kata Kunci: Informed-Consent, Nyawa-Pasien, Pertanggungjawaban-Pidana, Tenaga-Medis, Tenaga-Kesehatan.